CLINICAL AND LABORATORY FEATURES IN PATIENTS RECOVERED FROM COVID-19 PNEUMONIA (Multidisciplinary Journal of Science and Technology, 2026)
The post-acute sequelae of SARS-CoV-2 infection (Long COVID) represent a growing global health challenge. While acute phase laboratory changes are well-documented, the persistence of hematological and biochemical abnormalities months after recovery from COVID-19 pneumonia remains insufficiently characterized, particularly in the Central Asian population. A retrospective, cross-sectional cohort study was conducted involving 120 participants. The primary group consisted of 80 patients who had recovered from moderate to severe COVID-19 pneumonia 3 to 6 months prior to the study. The control group included 40 healthy individuals with no history of SARS-CoV-2 infection. Clinical data, complete blood counts, coagulation profiles, and systemic inflammatory markers were analyzed. Statistical evaluation was performed using the Student’s t-test and chi-square test. Patients in the post-COVID group demonstrated persistent laboratory alterations compared to the control group. Statistically significant elevations were observed in D-dimer (0.65 ± 0.08 mg/L vs. 0.22 ± 0.04 mg/L, p < 0.001), C-reactive protein (8.4 ± 1.2 mg/L vs. 2.5 ± 0.5 mg/L, p < 0.01), and ferritin (245 ± 25 mcg/L vs. 110 ± 15 mcg/L, p < 0.01). Furthermore, relative lymphopenia (21.5 ± 1.8% vs. 32.4 ± 2.1%, p < 0.05) remained prevalent in the recovered cohort. Recovery from the acute phase of COVID-19 pneumonia does not equate to complete physiological normalization. Persistent systemic inflammation and subclinical endotheliopathy can last for months, necessitating long-term clinical and laboratory monitoring to prevent delayed cardiovascular and pulmonary complications.